Bifunctional Solid Catalyst for Organic Reactions in Water: Simultaneous Anchoring of Acetylacetone Ligands and Amphiphilic Ionic Liquid "Tags" by Using a Dihydropyran Linker. Issue 17 (7th August 2018) - Lai, Bingbing; Mei, Fuming; Gu, Yanlong
Abstract: The use of solid catalysts to promote organic reactions in water faces the inherent difficulty of the poor mass‐transfer efficiency of organic substances in water, which is often responsible for insufficient reaction and low yields. To solve this problem, the solid surface can be manipulated to become amphiphilic. However, the introduction of surfactant‐like moieties onto the surface of silica‐based materials is not easy. By using an accessible dihydropyran derivative as a grafting linker, a surfactant‐combined bifunctional silica‐based solid catalyst that possessed an ionic liquid tail and a metal acetylacetonate moiety was prepared through a mild Lewis‐acid‐catalyzed ring‐opening reaction with a thiol‐functionalized silica. The surfactant‐combined silica‐supported metal acetylacetone catalysts displayed excellent catalytic activity in water for a range of reactions. The solid catalyst was also shown to be recyclable, and was reused several times without significant loss in activity. Abstract : Tag, you′re it : A recyclable bifunctional silica‐based solid catalyst that possessed both an ionic liquid tail and a metal acetylacetonate moiety was prepared through a mild Lewis‐acid‐catalyzed ring‐opening reaction of the dihydropyran with a thiol‐functionalized silica. This catalyst displayed superior catalytic activity in pure water for a range of organic reactions.